Respostas germinativas de sementes empregadas na semeadura direta e seus impactos frente às mudanças climáticas - Shiguehara, Ana Paula Ponce (Universidade Federal de São Carlos, 2024)
Climate change poses significant challenges to global ecosystems, particularly impacting seed germination in native forest species. This study investigates the germination response of 13 Brazilian forest species to simulated temperature regimes mimicking projected climate scenarios. Seeds were subjected to five temperature treatments, ranging from 25-50°C, and monitored for radicle emergence weekly. For the data analysis, each species included germination percentage (%G), Germination speed index (GSI) and Generalized Linear Mixed Models (GLMM). Preliminary results reveal varying germination responses across species, with some exhibiting decreased germination rates at higher temperatures. Species like Senegalia polyphylla (DC.) Britton showed resilience to temperature changes, while others, such as Guazuma ulmifolia Lam., displayed sensitivity to elevated temperatures. This research contributes to understanding the potential impacts of climate change on forest ecosystems and informs strategies for forest restoration and conservation.
Direct seeding seeds germination responses and their impacts on climate change
Keywords: Aquecimento global; Germinação de sementes; Temperatura.; Global warming; Seed germination; Temperature; CIENCIAS BIOLOGICAS::ECOLOGIA